Angola : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2018)
Lower oil prices since 2014 placed the Angolan economy under stress. The authorities initially reacted to the oil price shock with significant fiscal tightening and exchange rate adjustments coupled with foreign exchange quantitative restrictions. The policy mix in the run-up to the August 2017 elections-fiscal expansion and pegged exchange rate-led to a further erosion of fiscal and external buffers. The Government of President Joao Lourenco has focused attention on improving governance and restoring macroeconomic stability. The Government's macroeconomic stabilization program launched in early 2018 envisages: upfront fiscal consolidation; greater exchange rate flexibility; reducing the public debt-to-GDP ratio to 60 percent over the medium term; improving the public debt profile; settling domestic payments arrears; and strengthening the AML/CFT framework and ensuring its effective.